Effect of carnitine in diphtheria: A preliminary report - Soetono Soetono; Santoso Soeroso; Warsito Sutikno (Indonesian Pediatric Society, 1999)
A double placebo controlled trial was conducted on 68 diphtheriapatients who were hospitalized in pediatric ward of Kariadi Hospital, Semarang, from 1 April 1990 to 31 March 1991. The age range of the patients was between 7 months to 13 years, with the median of 48 months and the mean of 60.5 (SD 11) months. The pretreatmentcharacteristics of both groups were similar with respect to sex, the clinical condition on admission, presence of bullneck, nutritional and immunization status. Oral camitine was administered with a dose of 100 mg/kg/ day divided into 3 doses. Other standard treatment was administered to all patients. Post-treatment comparisons were performed on the prevalence of myocarditis, CK-MB level examined on the fifth day of treatment, and mortality. It was found that the prevalence of myocarditis and CK-MB levels' were significantly less than those in the placebo group, while the mortality in the carnitine group (3%) although smaller than in placebo group (17%) was not statistically different. It seems that 1-camitine is useful to prevent diphtheritic myocarditis,while its effect on improving the overall prognosis needs further study.